2002
DOI: 10.1124/jpet.302.1.240
|View full text |Cite
|
Sign up to set email alerts
|

Reconsideration of 5-Hydroxytryptamine (5-HT)7Receptor Distribution Using [3H]5-Carboxamidotryptamine and [3H]8-Hydroxy-2-(di-n-propylamino)tetraline: Analysis in Brain of 5-HT1AKnockout and 5-HT1A/1BDouble-Knockout Mice

Abstract: The characterization and anatomical distribution of 5-hydroxytryptamine (5-HT) 7 receptor binding sites in brain tissue has been hampered by the lack of a specific radioligand. In the present autoradiographic study, we took advantage of 5-HT 1A knockout and 5-HT 1A/1B double-knockout mice to revisit the pharmacological characterization and anatomical localization of 5-HT 7 binding sites in mouse brain using [ The 5-HT 7 receptor is the most recently identified member of the family of G protein-coupled 5-HT re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 37 publications
2
41
0
Order By: Relevance
“…To avoid the binding of [ 3 H]-8-OH-DPAT to 5-HT 7Rs , we used a concentration that does not bind to 5-HT 7Rs in 5-HT 1AR knockout mice. Bonaventure and colleagues [69] demonstrated that 1 or 2 nmol [ 3 H]-8-OH-DPAT does not bind or displays a very low binding density in the septal area of knockout mice compared to the moderate to high binding densities in the area of wild-type animals [69]. Consistently, lower K D values (1.3 nM, 95% confidence interval 0.35-2.25 nM) were obtained in the septum of wild-type animals than in that of knockout animals (5-HT 1AR knockout animals: 20 nM, 95% confidence interval 14-27 nM).…”
Section: Discussionmentioning
confidence: 98%
“…To avoid the binding of [ 3 H]-8-OH-DPAT to 5-HT 7Rs , we used a concentration that does not bind to 5-HT 7Rs in 5-HT 1AR knockout mice. Bonaventure and colleagues [69] demonstrated that 1 or 2 nmol [ 3 H]-8-OH-DPAT does not bind or displays a very low binding density in the septal area of knockout mice compared to the moderate to high binding densities in the area of wild-type animals [69]. Consistently, lower K D values (1.3 nM, 95% confidence interval 0.35-2.25 nM) were obtained in the septum of wild-type animals than in that of knockout animals (5-HT 1AR knockout animals: 20 nM, 95% confidence interval 14-27 nM).…”
Section: Discussionmentioning
confidence: 98%
“…This is supported by several observations. First, analysis of the brain regional distribution of 5-HT 7 receptor has revealed that this receptor is highly enriched in serotonergic neurons of dorsal raphe nuclei in adults (Neumaier et al, 2001;Bonaventure et al, 2002;Martín-Cora and Pazos, 2004). Together with the finding that the 5-HT 1A receptor has a higher affinity for forming heterodimeric (5-HT 1A -5-HT 7 ) rather than homodimeric (5-HT 1A -5-HT 1A ) complexes, this suggests that serotonergic neurons in raphe nuclei express a relative high level of heterodimers, i.e.…”
Section: Role Of Heterodimerization In Regulation Of 5-ht 1a Receptormentioning
confidence: 99%
“…However, a lack of impairment in the spatial Barnes maze task suggests that the 5-HT7 receptor is not critical for place learning in general [69]. In order to detect possible neuronal mechanisms underlying the observed learning deficit, Roberts et al studied synaptic plasticity within the CA1 region of the hippocampus, which is known to contain 5-HT7 receptorbinding sites [161]. Using paired pulse facilitation and paired pulse inhibition, it was observed that short-term plasticity was not altered in the 5-HT7 −/− mice.…”
Section: Memorymentioning
confidence: 97%